3D Printed Template‐Directed Assembly of Multiscale Graphene Structures. (20th January 2022) - Zhou, Jingzhuo; Wu, Xin; Chen, Yan; Yang, Chuang; Yang, Rui; Tan, Junyang; Liu, Yilun; Qiu, Ling; Cheng, Hui‐Ming
Abstract: The assembly of different levels of structure from the nano‐ to the macroscale has produced materials with outstanding performance. Here, using graphene as a model building block, the fabrication of multiscale structures is reported, with tailorable features spanning seven orders of magnitude in size by a 3D printed template‐directed assembly method which combines the ability to customize structures from the meso‐ to macroscale using digital light processing and from the nano‐ to microscale using self‐assembly. It is shown that by a careful design of the structures, a number of extraordinary properties can be produced including ultralow density (≥0.08 mg cm –3 ), and ultrahigh stiffness, and compressibility (full recovery from 95% strain). The approach not only provides diversified structure control over wide length scales for nanomaterial assembly but also shows the possibility of changing the properties of the structure for different applications. Abstract : Multiscale graphene architectures with five identifiable levels of structural hierarchy in length scale ranges from nanometer to centimeters (seven orders of magnitude) are created by an ingenious 3D printed template‐directed assembly method, which show customizable mechanical properties and multifunctionalities. The integrated method also demonstrates great potential to be applied to the assembly of other nanomaterials.